Honoring Culture and Voice By Empowering the Community: How a Grassroots Community Center Became the Waipahu Safe Haven - Greg Uchishiba; Vail Matsumoto; Stacy George; Stephanie Furuta (The University of Alabama, 2024)
Waipahu Safe Haven Immigrant/Migrant Resource Center (further referred to as Waipahu Safe Haven) was developed using an asset-based Community Center Model approach that acknowledged its community members' needs, funds of knowledge, and histories while drawing upon their individual and collective resiliency. This paper aims to outline the development of Waipahu Safe Haven and offer insights that can be valuable to others. It highlights a grassroots approach to fostering community empowerment, exemplified by creating a community center that adapts to meet the dynamic needs of the community. Key takeaways and lessons learned include respecting community relationships, leveraging the strengths of partnerships, and recognizing that members' voices and decision-making are essential. These lessons collectively enrich the understanding of individuals involved in sustained efforts to tackle pressing community issues in a culturally sensitive and inclusive matter. They also enrich the knowledge of those engaging in long-term work to address critical community needs in a culturally appropriate and inclusive way.